Prognosis of children with mixed phenotype acute leukemia treated on the basis of consistent immunophenotypic criteria - Mejstrikova, Ester; Volejnikova, Jana; Fronkova, Eva; Zdrahalova, Katerina; Kalina, Tomas; Sterba, Jaroslav; Jabali, Yahia; Mihal, Vladimir; Blazek, Bohumir; Cerna, Zdena; Prochazkova, Daniela; Hak, Jiri; et al. (Haematologica, 2010)
BACKGROUND: Mixed phenotype acute leukemia (MPAL) represents a diagnostic and therapeutic dilemma. The European Group for the Immunological Classification of Leukemias (EGIL) scoring system unambiguously defines MPAL expressing aberrant lineage markers. Discussions surrounding it have focused on scoring details, and information is limited regarding its biological, clinical and prognostic significance. The recent World Health Organization classification is simpler and could replace the EGIL scoring system after transformation into unambiguous guidelines. DESIGN AND METHODS: Simple immunophenotypic criteria were used to classify all cases of childhood acute leukemia in order to provide therapy directed against acute lymphoblastic leukemia or acute myeloid leukemia. Prognosis, genotype and immunoglobulin/T-cell receptor gene rearrangement status were analyzed. RESULTS: The incidences of MPAL were 28/582 and 4/107 for children treated with acute lymphoblastic leukemia and acute myeloid leukemia regimens, respectively. In immunophenotypic principal component analysis, MPAL treated as T-cell acute lymphoblastic leukemia clustered between cases of non-mixed T-cell acute lymphoblastic leukemia and acute myeloid leukemia, while other MPAL cases were included in the respective non-mixed B-cell progenitor acute lymphoblastic leukemia or acute myeloid leukemia clusters. Analogously, immunoglobulin/T-cell receptor gene rearrangements followed the expected pattern in patients treated as having acute myeloid leukemia (non-rearranged, 4/4) or as having B-cell progenitor acute lymphoblastic leukemia (rearranged, 20/20), but were missing in 3/5 analyzed cases of MPAL treated as having T-cell acute lymphobastic leukemia. In patients who received acute lymphoblastic leukemia treatment, the 5-year event-free survival of the MPAL cases was worse than that of the non-mixed cases (53+/-10% and 76+/-2% at 5 years, respectively, P=0.0075), with a more pronounced difference among B lineage cases. The small numbers of MPAL cases treated as T-cell acute lymphoblastic leukemia or as acute myeloid leukemia hampered separate statistics. We compared prognosis of all subsets with the prognosis of previously published cohorts. CONCLUSIONS: Simple immunophenotypic criteria are useful for therapy decisions in MPAL. In B lineage leukemia, MPAL confers poorer prognosis. However, our data do not justify a preferential use of current acute myeloid leukemia-based therapy in MPAL.
Keywords: fenotyp; Phenotype; Child, Preschool; leukemie; Adolescent; následné studie; prognóza; Infant; Child; dítě; Diagnosis, Differential; akutní myeloidní leukemie; akutní lymfatická leukemie; mladiství; receptory antigenů T-buněk; Follow-Up Studies; novorozenec; předškolní dítě; Receptors, Antigen, T-Cell; Leukemia; lidé; Immunophenotyping; Humans; Infant, Newborn; diferenciální diagnóza; kojenec; Prognosis; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Leukemia, Myeloid, Acute; imunofenotypizace